A meta-analysis of cognitive interventions for patients with recent onset psychosis: Are they effective for improving functioning? - Petkari, Eleni; Martín-María, Natalia; Sánchez-Gutiérrez, Teresa; Fernández-Castilla, Belén; Calvo, Ana (Psychological Medicine, 2023)
The increasing popularity of cognitive interventions for patients with psychosis calls for further exploration on how these interventions may benefit functional outcomes. We conducted a meta-analysis of randomized controlled trials (RCTs) to examine the effectiveness of cognitive interventions (i.e. Cognitive Remediation, Cognitive Training, Social Cognition, and their combination) on functioning of patients with recent onset psychosis, established as the period within the first five years from the first episode. The following databases were searched: Proquest, PUBMED/MEDLINE, PsycINFO, WOS, Scopus for research published until January 2022. In total, 12 studies were eligible. The total number of participants was 759, of which 32.2% in the intervention and 30.8% in the control group were female. We extracted data to calculate the standardized mean change from pre-test to post-test comparing the intervention with the control conditions. Overall, there was no effect of any of the cognitive intervention types on functioning. None of the examined factors (intervention type, length, and modality; control condition, follow-up time; cognitive functions; medication; symptoms) seemed to moderate these findings. Our results indicate that cognitive interventions as standalone interventions do not appear to improve functioning in patients with recent onset psychosis. Given the small number of eligible studies, further RCTs with larger and more refined samples are needed to test whether these interventions should be applied as single interventions with these patients.
Keywords: cognitive remediation; cognitive training; functioning; meta-analysis; recent onset psychosis; social cognition; JCR; Scopus